Community participation in bank of garbage: Explorative case study in Banyumas regency - Agnes Fitria Widiyanto; Rahab Rahab (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Waste bank is an activity that people do to reduce waste. The waste management activity through the establishment of a garbage bank becomes a very useful breakthrough, because people could save the waste which is exchangeable into money. The objective of this research is to know the inhibiting factors and the impetus for the community (targets) to participate in waste bank, covering behavior, knowledge, understanding, and community motivation. This research is an exploratory research with qualitative approach implemented in Banyumas district. Data collection is done through in-depth interviews using purposive sampling. Data were analyzed using interactive analysis. The results indicate that the presence of active waste banks in the community, as well as motivated by other community members. The development of the existing garbage bank in the society is unstable that there is a need to be support from various parties so that the garbage bank continues to progress and develop. Community knowledge of waste bank activities, including collection, transportation, community participation, prices or economic value of waste and recycling activities. Factors that encourage participation in waste banks, among others are motivation and environmental conscious behavior.